2008
DOI: 10.1093/toxsci/kfn111
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Induction of 28S Ribosomal RNA Cleavage by Ricin and the Trichothecenes Deoxynivalenol and T-2 Toxin in the Macrophage

Abstract: Ribosome-inactivating proteins (RIPs) and sesquiterpenoid trichothecene mycotoxins are known to bind to eukaryotic ribosomes, inhibit translation and activate mitogen-activated protein kinases. Here we compared the capacities of the RIP ricin to promote 28S ribosomal RNA (rRNA) cleavage with that of the trichothecenes, deoxynivalenol (DON), and T-2 toxin (T-2). In a cell-free model, exposure to ricin at 300 ng/ml for 30 min depurinated yeast 28S rRNA, however, neither DON (< or = 4 microg/ml) nor T-2 (< or = 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
48
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(50 citation statements)
references
References 59 publications
(62 reference statements)
2
48
0
Order By: Relevance
“…After binding with ribosomes, DON inhibits ribosomal peptidyl transferase, which prevents the initiation and elongation of the translation process (Shifrin and Anderson 1999). The inhibition of protein synthesis induced by DON can also result from the degradation of 28S rRNA (Li and Pestka 2008). Zhou et al (2003) demonstrated that DON can activate double-stranded RNA-associated protein kinase (PKR) which is responsible for the phosphorylation of the eukaryotic initiation factor 2α (eIF2α) and inhibition of translation.…”
Section: Introductionmentioning
confidence: 99%
“…After binding with ribosomes, DON inhibits ribosomal peptidyl transferase, which prevents the initiation and elongation of the translation process (Shifrin and Anderson 1999). The inhibition of protein synthesis induced by DON can also result from the degradation of 28S rRNA (Li and Pestka 2008). Zhou et al (2003) demonstrated that DON can activate double-stranded RNA-associated protein kinase (PKR) which is responsible for the phosphorylation of the eukaryotic initiation factor 2α (eIF2α) and inhibition of translation.…”
Section: Introductionmentioning
confidence: 99%
“…In the macrophage, DON induced mobilization of MAPKs to the ribosome (13) and promoted 28S rRNA cleavage at the peptidyltransferase center (14), suggesting that ribosome interactions of trichothecenes play an important role in their cytotoxicity.…”
mentioning
confidence: 99%
“…This toxin has a broad spectrum of effects on the gastrointestinal, reproductive and neuroendocrine systems in mammals and especially the immune system [2,3]. DON is known to inhibit protein synthesis by binding to the peptidyltransferase region of the 28S ribosomal RNA resulting in ribotoxic stress [4]. It has a major effect on actively dividing cells including bone marrow, spleen and thymus cells [5].…”
Section: Introductionmentioning
confidence: 99%
“…With respect to the strongest correlation to phenotype, metabolites (unlike genes and proteins, whose function is determined by epigenetic regulation or posttranslational modification) are the end products of cellular regulatory processes and their levels can be regarded as the ultimate response of a biological system to genetic or environmental changes [9].Metabolomics represents the global assessment of metabolites in a biological sample and defines the information closest to the M A N U S C R I P T A C C E P T E D ACCEPTED MANUSCRIPT 4 phenotype of the biological system under study [10].The metabolome is defined as the full complement of small-molecule metabolites found in a specific cell, organ, or organism [11]. It is an excellent indicator of phenotypic heterogeneity and has been recognized as a key factor in rare-cell survival when populations are subjected to major chemical or environmental challenges [12].…”
Section: Introductionmentioning
confidence: 99%